Impact of travel distance and experience use history on visitors' climate friendly behavior and support for climate friendly management action. Issue 6 (28th November 2020) - Xu, Shuangyu; Stanis, Sonja Wilhelm; Zhang, Hongchao; Groshong, Lisa; Morgan, Mark
Abstract: Despite growing concern about climate change and the potential impacts of tourism on the environment, little is known about visitor responses toward climate mitigation strategies in nature-based tourism settings or factors that influence them. This study examined the influence of travel distance and Experience Use History (EUH) on visitor willingness to engage in climate friendly behavior in state parks and their support for management actions to minimize climate change impacts. Following a stratified-cluster sampling approach, a total of 1, 775 visitors (69.7% response rate) completed online or paper surveys at 20 pre-selected Missouri state parks and historic sites. Results indicated that visitors living within 100 miles of these locations were more willing to engage in climate friendly behavior, but less supportive of climate friendly management actions, as compared to those living farther away. Visitors' EUH was only associated with their willingness to engage in climate friendly behavior, but not with support for climate friendly management actions. In addition to some theoretical and methodological contributions, this paper sheds light on management of nature-based tourism destinations such as state parks.